2013
DOI: 10.1038/ncomms3229
|View full text |Cite
|
Sign up to set email alerts
|

The origin of antiferroelectricity in PbZrO3

Abstract: Antiferroelectrics are essential ingredients for the widely applied piezoelectric and ferroelectric materials: the most common ferroelectric, lead zirconate titanate is an alloy of the ferroelectric lead titanate and the antiferroelectric lead zirconate. Antiferroelectrics themselves are useful in large digital displacement transducers and energy-storage capacitors. Despite their technological importance, the reason why materials become antiferroelectric has remained allusive since their first discovery. Here … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

18
289
1
9

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 291 publications
(317 citation statements)
references
References 31 publications
18
289
1
9
Order By: Relevance
“…In systems with real incommensurate phases it often happens that the generally incommensurate modulation is pinned down to the particular commensurate wavevector. The terms in the free energy expansion responsible for this effect are called Umklapp terms 4,24 . In PbZrO 3 we assume the Umklapp terms to be strong enough to drive the phase transition directly to the commensurate AFE state, skipping the incommensurate phase.…”
Section: Modulation Instabilitymentioning
confidence: 99%
See 2 more Smart Citations
“…In systems with real incommensurate phases it often happens that the generally incommensurate modulation is pinned down to the particular commensurate wavevector. The terms in the free energy expansion responsible for this effect are called Umklapp terms 4,24 . In PbZrO 3 we assume the Umklapp terms to be strong enough to drive the phase transition directly to the commensurate AFE state, skipping the incommensurate phase.…”
Section: Modulation Instabilitymentioning
confidence: 99%
“…Both the phenomenon itself and its underlying mechanisms are currently under intense investigation and review [2][3][4][5][6][7] . Kittel 8 initially assigned the term "antiferroelectric" to the crystal that has a structural phase transition from a highersymmetry nonpolar parent phase to a lower-symmetry nonpolar phase, distinguished from the parent phase by the anti-parallel ionic shifts.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since the value of 1/4 is not stimulated by symmetry, it can be changed by either external perturbations or changes in chemical composition. This important symmetry aspect has been recently highlighted by Tagantsev et al in the study of lattice dynamics of PbZrO 3 [27]. These authors concluded that the antiferroelectric state is a so-called missed incommensurate phase and that the transition to this state is driven by softening of a single polar lattice mode.…”
Section: A Crystal Structurementioning
confidence: 84%
“…Due to flexoelectric coupling, the system is expected to be virtually unstable against the incommensurate modulation, as was shown by Axe et al [28]. However, the Umklapp interaction forces the system to go directly to the commensurate lock-in phase, leaving the incommensurate phase as a missed opportunity [27].…”
Section: A Crystal Structurementioning
confidence: 93%